How Working for a Small Family Business Impacts Employee Satisfaction and Performance - Echevarria, Sloane N (East Carolina University, 2017)
I am studying performance and job satisfaction of family member and non-family member employees in a family-run business. The purpose of this study is to see how employees are affected when they work for a family business and to explore whether employees are more or less motivated to work for the family firm. This study shows how working for a family business has an impact on an employee’s performance based on the care and consideration received from the family that owns the business, and whether it leads to more or less organizational commitment. To gather data for my research project, I conducted interviews with 15 employees of a local family restaurant. The interviewees included both family-member and non-family-member employees to compare perceptions of management as well as general morale and satisfaction working for the company. The study found that nonfamily employees were more motivated to serve customers and were more committed to their work than family members. My research project helps to identify the advantages and disadvantages of working for a family firm. It also creates a deeper understanding of how different business operating structures impact employees and overall business performance.
Keywords: Family; Business; Management; Performance; Satisfaction